2022
DOI: 10.3390/cleantechnol4030042
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Magnesium Impregnation of Avocado Seed Biochar for Aqueous Phosphate Removal

Abstract: There has been increasing interest in using biochar for nutrient removal from water, and its application for anionic nutrient removal such as in phosphate (PO43−) necessitates surface modifications of raw biochar. This study produced avocado seed biochar (AB), impregnated Fe- or Mg-(hydr)oxide onto biochar (post-pyrolysis), and tested their performance for aqueous phosphate removal. The Fe- or Mg-loaded biochar was prepared in either high (1:8 of biochar to metal salt in terms of mass ratio) or low (1:2) loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The porous structure of biochar also can retain water and nutrients, which can help reduce nutrient runoff and soil erosion. Studies have shown that biochar from avocado seeds impregnated with Mg-(hydr)oxide (postpyrolysis) demonstrated the benefits of metal impregnation regarding enhancing phosphate adsorption and its potential use for water treatment due to its performance for aqueous phosphate removal [99].…”
Section: Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…The porous structure of biochar also can retain water and nutrients, which can help reduce nutrient runoff and soil erosion. Studies have shown that biochar from avocado seeds impregnated with Mg-(hydr)oxide (postpyrolysis) demonstrated the benefits of metal impregnation regarding enhancing phosphate adsorption and its potential use for water treatment due to its performance for aqueous phosphate removal [99].…”
Section: Biocharmentioning
confidence: 99%
“…Composting seems to be the easier and cheaper alternative for avocado waste management. However, it can be a challenge due to some limitations, including (i) time and space requirements: composting requires time and space to allow the waste to decompose and transform into a usable product; (ii) high moisture content makes it difficult to compost it without the addition of dry organic materials such as straw or wood chips; (iii) improper composting process can result in a product with pathogen microorganisms such as Escherichia coli and Salmonella; and (iv) variability in composition, due to the composition of avocado waste can vary depending on factors such as the variety of avocado, the stage of ripeness, and the method of processing, which can affect the quality and consistency of the compost [70,99,101].…”
Section: Liquid Biofertilizersmentioning
confidence: 99%
“…Studies have indicated that such limitation of pristine biochar can be improved by surface modifications. [9][10] For instance, modification of biochar with magnesium (Mg/ biochar), [11][12] iron (FeO/biochar), [13] and aluminum (Al 2 O 3 / biochar) [13] resulted in improved adsorption efficiency. The adsorption performance of biochar can be further improved by reducing its size to the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…For the current treatise, waste of avocado stones (AVSs) was selected as a biochar source (AVS-BC). The worldwide annual production of avocado exceeds 6.4 × 10 6 t. The stone (comprising the seed) constitutes 14-24% of the fruit, and the rest of the fruit is the peel and the pulp (García-Vargas et al 2020, Kang et al 2022. By and large, composting services do not accept the AVS which is hard to grind.…”
Section: Introductionmentioning
confidence: 99%